Senior academics as key negotiators in the implementation of impact policies in the social sciences and humanities - Vanholsbeeck, Marc; Demetriou, Theodosia; Girkontaite, Agne; Starcic, Andreja Istenic; Keiski, Ville; Kulczycki, Emanuel; Papanastasiou, Elena; Pölönen, Janne; Proppe, Hulda; Vehovec, Maja (My University, 2019)
In this paper, we pursue two main objectives. First, we review the relevant literature and present it according to a theoretical framework that combines structural perspectives and consideration for individual agency, to allow us a better understanding of the role played by senior academics in the social sciences and humanities (SSH) in the implementation of the different policies that concern the production, the dissemination and the evaluation of research, including impact related policies. Indeed the academics’ negotiating power of the impact agenda – as it is currently promoted by European policy makers (see e.g. European Commission 2018) and encompasses the impact on policy making, economy as well as the environment and society – cannot be understood in isolation of their perception and attitudes towards the broader political changes that affect the practice of academic research. Secondly we discuss some preliminary results from the interviews we have conducted in the context of the COST ENRESSH action with 16 European senior sociologists active in eight European countries, focusing here on their perceptions and attitudes towards the impact agenda.
This article is based on work from COST Action 15137 European Network for Research Evaluation in the SSH (ENRESSH) and supported by COST (European Cooperation in Science and Technology).
Keywords: research policy; impact; social sciences and humanities; senior academics